Вербалізація концепту любов/кохання як духовної цінності в поетичному мовленні Віктора Бойка (на матеріалах збірки "Пролог") - Черненко, Ольга Ігорівна (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2017)
У статті висвітлено категорію духовної цінності любов/кохання як складника поетичної мовної картини світу Віктора Бойка, визначені контексти, у яких есплікується поняття духовної цінності, розмежовано сфери кохання й любові. Також окреслено специфіку образно-метафоричного мовлення поета, що визначає його творчу індивідуальність та ідіостиль. Сконцентровано увагу на формуванні світогляду митця на початку творчого шляху, а також на його власному розумінні любові/кохання як однієї з найважливіших загальнолюдських й особистісних цінностей.

In the article the concept of moral value of love is examined as a one of the notional in language mapping of the world of Victor Boyko. In his poetry the concept of moral value is certained, spheres love / to be in love are differentiated. Also the specific of poet’s figuratively-metaphorical language determines his creative individuality and individual style. The aim of research is to identify the expression features of moral value love / to be in love in Victor Boyko’s poetry discourse. The task of research is to set up dominants for an individual style of Victor Boyko’s poetry; to define a sphere of moral values in the contexts; to separate the sphere that is common for all personality values in the poetic discource of the Victor Boyko’s poetry. The work has general orientation on modern researches of poetic discourse in the linguistics, where the poetic texts are analyzed as the carriers of certain system of moral value as the special form of communication, that allows to reconstruct the poet’s individual style. In the work the poet’s worldview is represented; the specificity of the figurative language which is one of the determinants of the poet’s artistic individuality, his own individual style is defined. In the conclusions of the research it is paid attention on forming of poet’s world view at the beginning of his creative way, and also determination to love as one of major common to all mankind and personality values.
Love as Moral Value in Victor Boyko’s Poetry Discourse
Keywords: мова; творча індивідуальність; мовна картина світу; ідіостиль; language; creative individuality; language world-mapping; individual style